2011
DOI: 10.1007/s00011-011-0335-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of NADPH oxidase-mediated activation of Jak2/Stat3 and mitogen-activated protein kinases and expression of TGF-β1 in the pathophysiology of acute pancreatitis

Abstract: Inhibition of NADPH oxidase may be beneficial for prevention and treatment of pancreatitis by suppressing Jak2/Stat3 and MAPKs and expression of TGF-β1 in pancreatic acinar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…Recently, it was reported that NOX4-derived ROS mediated inhibition of protein-tyrosine phosphatases, resulting in sustained activation of JAK2-STAT1/3 (48). Similarly, treatment with DPI, an inhibitor of flavoprotein-dependent oxidases such as NOX, was previously shown to suppress activation of JAK2-STAT3 (28), and inhibition of the NOX subunit p47 phox was found to abolish angiotensin II-induced JAK-STAT3 activation (49), implicating ROS in JAK-STAT3 activation. Thus, one interesting possibility is that BLT2-NOX4-derived ROS sustain the phosphorylated (activated) state of JAK2-STAT3 by inactivating protein-tyrosine phosphatases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, it was reported that NOX4-derived ROS mediated inhibition of protein-tyrosine phosphatases, resulting in sustained activation of JAK2-STAT1/3 (48). Similarly, treatment with DPI, an inhibitor of flavoprotein-dependent oxidases such as NOX, was previously shown to suppress activation of JAK2-STAT3 (28), and inhibition of the NOX subunit p47 phox was found to abolish angiotensin II-induced JAK-STAT3 activation (49), implicating ROS in JAK-STAT3 activation. Thus, one interesting possibility is that BLT2-NOX4-derived ROS sustain the phosphorylated (activated) state of JAK2-STAT3 by inactivating protein-tyrosine phosphatases.…”
Section: Discussionmentioning
confidence: 97%
“…5). STAT3 has previously been shown to be of potential prognostic relevance in ovarian cancer (11,28,29,41). In particular, activation of STAT3 and its translocation to the nucleus are frequent events in ovarian carcinoma (41), and the levels of phosphorylated STAT3 were found to correlate with disease stage, differentiation of carcinoma, and the presence of lymph node metastasis (11).…”
Section: Discussionmentioning
confidence: 99%
“…Binding of STAT3 to DNA in nuclear extracts was assessed by EMSA with double-stranded deoxyoligonucleotides specific for STAT3 consensus sequence 5′-GATCCTTCTGGGAATTCC TAGATC-3′, which was labelled on the 3′ end with biotin (Ju et al, 2011). EMSA was carried out using the Lightshift kit (Thermo Fisher Scientific Inc., Rockford City, IL, USA).…”
Section: Stat3/dna Binding Assaymentioning
confidence: 99%
“…Preparation of nuclear extracts and electrophoretic mobility shift assay (EMSA) for Stat3-DNA binding activity Preparation of nuclear extracts and EMSA for Stat3-DNA binding activity were carried out following the methods reported by Ju et al [33]. The cells were lysed in the buffer containing 10 mM HEPES, 10 mM KCl, 0.1 mM ethylenediaminetetraacetic acid (EDTA), 1.5 mM MgCl 2 , 0.2% Nonidet P-40, 1 mM dithiothreitol (DTT), and 0.5 mM phenylmethylsulfonylfluoride (PMSF), and centrifuged at 12,000g for 20 min.…”
Section: Measurement Of Ros Generationmentioning
confidence: 99%